Adsorption of reactive dye on seawater-neutralised bauxite refinery residue - de Souza, Kelli Cristina [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Couperthwaite, Sara Jane; da Conceição, Fabiano Tomazini [UNESP]; de Barros, Thalita Rangueri [UNESP]; Frost, Ray (Elsevier, 2013)
This investigation has demonstrated the need for thermal treatment of seawater neutralised red mud (SWRM) in order to obtain reasonable adsorption of Reactive Blue dye 19 (RB 19). Thermal treatment results in a greater surface area, which results in an increased adsorption capacity due to more available adsorption sites. Adsorption of RB 19 has been found to be best achieved in acidic conditions using SWNRM400 (heated to 400 °C) with an adsorption capacity of 416.7. mg/g compared to 250.0. mg/g for untreated SWNRM. Kinetic studies indicate a pseudosecond-order reaction mechanism is responsible for the adsorption of RB 19 using SWNRM, which indicates adsorption occurs by electrostatic interactions. © 2013 Elsevier Inc.
Keywords: Adsorption; Reactive Blue dye; Seawater neutralised red mud; Thermal treatment; Acidic conditions; Adsorption capacities; Adsorption site; Pseudo second order; Reaction mechanism; Reactive blues; Red mud; Refinery residues; Heat treatment; Seawater; dye; sea water; adsorption kinetics; environmental parameters; heating; molecular interaction; priority journal; seawater neutralised red mud; static electricity; surface property; thermal analysis